**Can you put the following steps in order?**

Check by substituting the variable with the solution / answer

Divide or Multiply on both sides of the equal sign(Division or Multiplication Property)

Combine Like Terms on both sides of the equal sign

Distribute Coefficient(s) (Distributive Property)

Add a positive or a negative on both sides of the equal sign(Addition Property)

* * * *

**Steps in the Correct Order:**

1. Distribute Coefficient(s)

2. Combine Like Terms on both sides of the equal sign

3. Add a positive or a negative on both sides of the equal sign

4. Divide or /multiply on both sides of the equal sign

5. Check by substituting the variable with the solution / answer

**Do you know the purpose of each step?**

1. Distribute Coefficient(s) (Distributive Property)

**To eliminate parentheses**

2. Combine Like Terms on both sides of the equal sign

**To total like terms on both sides of the equal sign**

3. Add a positive or a negative on both sides of the equal sign

**To isolate the variable or variable term (for example X or 5X)**

4. Divide or /multiply on both sides of the equal sign

**To isolate the coefficient from the variable term if necessary**

5. Check by substituting the variable with the solution / answer

**To verify the solution balances the equation; if so, the check confirms the solution is correct.**

**Here are two mnemonics to remember the order of the steps to solve an equation?**

**D**aily

**C**alculating

**A**'s

**D**oing

**M**ath

**C**arefully

or

**D**aisy

**C**hews

**A**lmonds

**M**ooing

**C**ontinuously

**Let's Practice!**

5m + 2(2m + 3) = -20 - m – 4

• Distribute

5m + 2(2m + 3) = -20 - m – 4

• Distribute

• Results = => 5m + 4m + 6 = -20 –m - 4

•

**Combine**

• Results = => 9m + 6 = -24 - m

•

**Add (+m) on both sides**

• Results = => 10m + 6 = -24

•

**Add (-6) on both sides**

• Results = => 10m = -30

•

**Divide by 10 on both sides**

• Solution =>

**m= -3**

**Check:**

5m + 2(2m + 3) = -20 - m – 4

5m + 2(2m + 3) = -20 - m – 4

5(-3) + 2(2(-3) + 3 ) = -20 – (-3) – 4

5(-3) + 2(-6 + 3) = (-21)

5(-3) + 2(-3) = (- 21)

(-21) = (-21)

Since both sides of the equation have the same number, the equation is balanced. Therefore the solution m = (-3) is correct.